PENGEMBANGAN MODULPENDIDIKAN AGAMA ISLAMDI SEKOLAH DASAR LUAR BIASA TUNAGHITA RINGAN (C)SLB BHAKTI KENCANA BERBAH SLEMAN - Fitriyah Rohmatin (Islamic University of Indonesia, 2017)
This research aims to: (1) review textbooks used in PAI learning students superb mild mental retardation SLB Bhakti Kencana Berbah, (2) review compliance with the condition of PAI textbook elementary school students superb mild mental retardation, (3) hold the development of learning modules that comply with elementary school students an incredible class I mild mental retardation. This research is a research and development (R&D), with the aim of developing learning modules for PIE. The research model is used to produce a particular product, and testing kefektifan product. As for who will be developed in this research is the 4-D model (Four-D models). This model consists of four stages of development, namely depine (definition), design (Design), develop (development), and desseminate (Spread). Implementation of research and development using the method diskriptif, evaluative, and experimental. The subject test 7 students, both early stage or both. Testing instruments in the form of sheet material for expert validation, media experts, colleagues, friends, teachers and student response. The results showed that: (1) design learning materials of the existing Islam textbook used at Special Elementary school for children with Mild mental Retardation (SDLB C) is the same as with public schools which refers to the 2006 curriculumn (KTSP) is terms, of the standard (SI) Standard, askomptensi (SK), and basic competence (KD). (2) The existing textbook has very difficult material to form with the condition and capability of the students. (3) the product validation was performed for the design model of the developed module before it was tested and obtained good result. The validation was conducted by the material expert, media expert, colleague, class teachers, and students. After being tested in the initial ang second stages, the module quality reviewed from the aspects of content, language, pictures, presentation,and images, as well as serving good quality Sedn kegrafisaa aspects, i.e. in accordance with the characteristics and abilities of the students, so that the feasibility for elementary school students superb mild mental retardation (C) SLB Bhakti kencana. Keywords: development, module, Islamic education, SDLB C